Quadruple sulfur isotope biosignatures from terrestrial Mars analogue systems. (1st September 2021) - Moreras-Marti, A.; Fox-Powell, M.; Stueeken, E.; Di Rocco, T.; Galloway, T.; Osinski, G.R.; Cousins, C.R.; Zerkle, A.L.
Abstract: In this study, we present quadruple sulfur isotope values (QSI: 32 S, 33 S, 34 S, 36 S) measured in sediments from two sulfur-rich Mars analogue environments: i) the glacially-fed hydrothermal pools in Iceland (Kerlingarfjöll and Kverkfjöll), and ii) the Lost Hammer hypersaline spring from Axel Heiberg Island, Nunavut, Canada. The localities host different physical and geochemical characteristics, including aqueous geochemistry, volcanic input, temperature, pH and salinity. The δ 34 S values of sulfur compounds from the Lost Hammer hypersaline spring exhibit large fractionations typical of microbial sulfate reduction (MSR) with or without additional oxidative sulfur cycling and microbial sulfur disproportionation (MSD) ( 34 εSO4-CRS from −49.5 to −43.5‰), contrary to the small S isotope fractionations reported for the Icelandic hydrothermal sites ( 34 εSO4-CRS from −9.9 to −0.7‰). Lost Hammer minor S isotope values (Δ 33 S and Δ 36 S), interpreted within the context of a sulfur cycling box model, are consistent with a biogeochemical S cycle including both MSR and MSD. In contrast, the small range in δ 34 S values within the Iceland hydrothermal pools are consistent with a large volcanic H2 S flux and minimal biological S cycling. The minor S isotope values recorded in the hydrothermal pools, however, indicate further biogeochemical sulfur cycling. Our results demonstrate that contrasting physical and chemical characteristics between sites support different microbial S cycling processes, as recorded in the QSI sedimentary values. The QSI data and the derived models support the strong potential for QSI values to be used as biosignatures in the search for life in Martian S-rich environments. These results also suggests that extreme, metabolic energy-limited environments with low abiotic sulfur fluxes could be more likely to produce unequivocal biological QSI signals than those with more moderate conditions or abundant available energy. This finding carries significant implications for targeting sites on Mars for in situ measurements or future sample return missions.